Avīzes ,,Segodņa" jaunāko ziņu reprezentācija (1919. un 1925. gads) - Šmeļovs, Romans (Latvijas Universitāte, 2010)
Darbs veltīts 1919. un 1925. gadu avīzē „Segodnja” zinu materiāla reprezentācijai. Autors salīdzina avīzes „Segodnja” izdevēju izmantoto stratēgiju reprezentējot notikumus sagatavojot kārtējo noteikta laika perioda numurus. Pirmajā izpētes dalā autors nosaka izmantotas jēdzienus, tādus kā „zinu materiāls”, „notikums”, „normas”. Otra dala veltīta noteiktā perioda zinu materiāla analīzei.

The paper is devoted to the research of the representation of news in newspaper “Segodnya” n 1919 and 1925 y.y. The author makes a comparison of strategies which editors of “Segodnya” used to consider while newspaper was issued. The first chapter of paper examines concepts which author involves in his research, such as “news”, “event”, “normalcy”. The second part of research is devoted to analysis of news in 1919 and 1925 y.y. The research can be interesting to philologists, dealing with evolution of Russian press in Latvia during the first half of XX century, as well as to all inquisitive readers.
News Representation in Newspaper ,,Segodnya" for 1919 and 1925
Keywords: Filoloģija